Do commonly available round facemasks fit near-term and term infants?. Issue 4 (21st September 2019) - Haase, Bianca; Badinska, Ana Maria; Koos, Bernd; Poets, Christian F; Lorenz, Laila
Abstract : Objective: With inappropriately large facemasks, it is more difficult to create a seal on the face, potentially leading to ineffective ventilation during neonatal stabilisation. We investigated whether commonly available round facemasks are of appropriate size by measuring facial dimensions in near-term and term infants using two-dimensional (2D) and three-dimensional (3D) images. Design: Prospective single-centre observational study. Setting: Infants born in our centre at 34–41 weeks' gestation were eligible. Intervention: Patients were photographed with 2D and 3D technique. Main outcome measures: Distances between nasion and gnathion were measured and compared with the outer diameter of various round facemasks. Methods: 2D and 3D images were performed using standard equipment. Correlations between gestational age and the above-mentioned distances were assessed using Pearson's r. Results: Images were taken from 102 infants with a mean (SD) gestational age of 37.9 (2.3) weeks. Mean distance between nasion and gnathion was 46.9 mm (5.1) in 2D and 49.9 mm (4.1) in 3D images, that is, on average 3 mm smaller in 2D than with 3D (p<0.01). Based on these measurements, round facemasks with an external diameter of 50 mm seemed fitting for most (61%) term infants and 42 mm masks for most (72%) near-term infants (GA 34–36 weeks). Conclusions: Round facemasks with an external diameter of 60 mm are too large for almost all newborn infants, while 42/50 mm round facemasks are well fitting. Important anatomical structures were only visible using 3D images. Clinical trial registration number: NCT03369028